Seven Tools untuk Menurunkan Kecacatan pada Produk Kopi - Moh Ririn Rosyidi; Nailul Izzah; Thoriq Kamil Najahi (Universitas Teuku Umar, 2020)
An increasingly competitive industrial era to maintain and increase interest in buying and selling products to consumers is very important, every business actor wants to how to win the competition in the business so that they can exist in this field by maintaining the quality of the products to be marketed. The coffee products in the company have three defects, namely damaged packaging containers, inappropriate weight, and coarse coffee grounds. The seven tools method will determine the causes of defects in coffee products. From the analysis of the Check Sheet table, it is known that there are three types of defects. From the histogram, it is known that the most defect data distribution is the damaged packaging containers of 1252 pcs, P control chart, it is known that the UCL value is 0.2993 and LCL -0.1525 these values are within the control limit. Pareto diagram shows that the most dominant type of defect is WKR (53.97%). Correlation calculations using the Scatter diagram obtained a value of -7.380. This value shows that the two relationships between defective packaging containers and coarse coffee grounds have a negative relationship. From the Fishbone diagram and RCA analysis, it is known that the causes of disability with the highest WKR are man, machine, method, and material factors. Corrective action, namely the need to change the packaging, provide breeding to the operator, provide training, and maintain the machine so that the engine remains in good condition.